A study of optical fiber and comparison with metallic cable in communication / Mohamad Zuki Abdullah - Abdullah, Mohamad Zuki (1991)
This project is to study about Fiber Optic Communication Systen and make a comparison with the conventional system using metallic cable. In Fiber Optic system, the electric signal at the transmitter will convert to light signal by the Source and it will transmit through a fiber cable, and at the receiver side this light signal will detect by a light detector and it will convert back to electrical signal. In the conventional system, the electric signal will transmit either via a metallic cable or microwave.